PENGARUH CAREER ADAPTABILITY DAN SELF-EFFICACY TERHADAP KESIAPAN KARIER SISWA SMK DI KOTA AMBON - Rusnawati Ellis; Neleke Huliselan; Eva Dwi Mariska; Wahyuni Renuat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the influence of Career adaptability and self-efficacy on career readiness among vocational high school (SMK) students in Ambon City. The research involved 200 grade XII students selected through simple random sampling. This quantitative study employed a multiple regression analysis. Data were collected using three standardized instruments: Career Adapt-Abilities Scale (CAAS), General Self-efficacy Scale (GSE), and Career Readiness Scale. The results showed that Career adaptability had a positive and significant effect on career readiness (β = 0.487, p < 0.001), while self-efficacy did not show a significant effect (p = 0.532). Simultaneously, both variables significantly influenced career readiness (F = 28.402, p < 0.001) and explained 22.4% of the variance. These findings indicate that Career adaptability is a stronger predictor of career readiness than general self-efficacy among SMK students in Ambon. The study suggests the importance of developing Career adaptability programs in vocational education, especially in eastern Indonesia.